Potential roles of cigarette smoking on gut microbiota profile among Chinese men - Jiayao Fan; Fangfang Zeng; Haili Zhong; Jun Cai; Wentao Shen; Chunxiao Cheng; Chunfeng He; Yuanjiao Liu; Yuan Zhou; Shujie Chen; Yimin Zhu; Tao Liu; et al. (BMC Medicine)
Abstract Background Cigarette smoking is posited as a potential factor in disrupting the balance of the human gut microbiota. However, existing studies with limited sample size have yielded inconclusive results. Methods Here, we assessed the association between cigarette smoking and gut microbial profile among Chinese males from four independent studies (N total = 3308). Both 16S rRNA and shotgun metagenomic sequencing methods were employed, covering 206 genera and 237 species. Microbial diversity and abundance were compared among non-smokers, current smokers, and former smokers. Results Actinomyces[g], Atopobium[g], Haemophilus[g], Turicibacter[g], and Lachnospira[g] were found to be associated with smoking status (current smokers vs. non-smokers). Metagenomic data provided a higher resolution at the species level, particularly for the Actinomyces[g] branch. Additionally, serum γ-glutamylcysteine (γ-Glu-Cys) was found to have a potential role in connecting smoking and Actinomyces[g]. Furthermore, we revealed putative mediation roles of the gut microbiome in the associations between smoking and common diseases including cholecystitis and type 2 diabetes. Conclusions We characterized the gut microbiota profile in male smokers and further revealed their potential involvement in mediating the impact of smoking on health outcomes. These findings advance our understanding of the intricate association between cigarette smoking and the gut microbiome.